STREAM OF CONSCIOUSNESS STYLE IN KINCAID’S 'WHAT I’VE BEEN DOING LATELY' - Yustin Sartika (Leksema: Jurnal Bahasa dan Sastra, 2016)
Stream of consciousness is used by writers of fiction for presenting characters’ thought and feeling. It allows the readers to experience the characters’ emotion thought from inside a character’s head. This article aimed to find out the use of Stream of Consciousness in What I’ve Been Doing Lately short story by Jamaica Kincaid. Kincaid successfully reflects characters’ mental experiences through interior monologue. Some literary devices are used to strengthen the power of stream of consciousness. She uses foreshadowing and repetition to illustrate pessimistic thought of the character.